Maximizing wireless power transfer efficiency at exceptional points - Wei-Kang Hu; Bowang Zhang; Youhao Hu; Haoxiang Li; Wei Han (Communications Engineering)
Abstract Magnetically coupled wireless power transfer (WPT) technology has been applied in stationary consumer electronics and holds great potential for charging traveling electric vehicles. The efficiency of WPT systems is, however, inherently vulnerable to changes in coupling and load conditions. Previous studies have underscored the robustness of parity-time (PT) symmetric WPT systems against variations in coupling strength within the exact PT region. In this study, by treating the loss rate as an adjustable parameter, we unveil that the efficiency of a PT-symmetric WPT system reaches its peak at the exceptional point (EP). Through adaptive adjustment of the virtual loss rate that pins the system at the EP, we can uphold maximum‐efficiency, frequency‐stable power transfer under a broad range of coupling and load conditions. Our EP-pinning strategy offers a significant advantage over conventional schemes that require on-site measurement of coupling strength and loss rates. The discovery of EP-induced efficient power transfer should facilitate the future deployment of wireless charging infrastructure.